Analisis Peraturan Pemerintah No. 11 Tahun 2017 Tentang Management Pegawai Negeri Sipil Terhadap Mutasi Pns Antar Instansi Di Pemerintah Daerah Asahan - R.W, Syamsuar; Manurung, Mangaraja (Universitas Islam Sumatera Utara, 2024)
The implementation of mutations is a policy regulated by the government to improve public services and government administration functions. Transfers between agencies in Asahan Regency are carried out by rotating employees and fulfilling needs according to competency, educational background and performance assessment. It is hoped that civil servant transfers will have a better impact on regional administration. The research method used in this thesis analysis is an empirical legal research method with the primary material being interview studies and observations through direct observation and receiving information from respondents. The results of research conducted by the author in analyzing the implementation of Civil Servant transfers between agencies in Asahan Regency, show that the role of civil servant transfers between agencies in the Asahan Regency Government aims to optimize the performance of agencies in Asahan Regency, including technical staff, teachers and health workers. That the existence of an inter-agency transfer system can meet the needs and shortcomings of civil servants in Asahan Regency in accordance with the performance, educational background and competencies possessed by Civil Servants. The obstacles faced in the Civil Servant mutation process are in accordance with the author's direct observation that Civil Servants who wish to apply for a mutation do not understand the procedures and requirements for submitting a mutation, apart from that, civil servants who are in the 2018 formation cannot apply. transfer because they have to follow the provisions in Government Regulation Number 11 of 2017 concerning Management of Civil Servants. Keywords: Mutations, civil servants, between agencies, Asahan Regency